Cultivation Of Tomato Vegetables By Watering Under A Black Polyethylene Film - Ilxamov Nortoy Muradovich; Ganiyev Sanjar Ernazarovich; Toshpulatov Chingizxon Vali o’g’li (Zien Journals, 2022)
In the world of Agriculture, a wide range of scientific research is being carried out to reduce water consumption in irrigation of crops, to investigate the level of soil moisture and water consumption in various irrigation methods, to improve and increase fertility of soil agrophysical, agrochemical and microbiological properties, as well as to increase the yield of vegetable crops in various irrigation methods and Development, improvement and wide introduction into practice of optimal economical irrigation methods in the care of planting vegetable crops in spring and summer terms in conditions of water shortage is considered as one of the pressing issues in agriculture, reducing water consumption in irrigation of crops, investigation of soil moisture levels and water consumption in various irrigation methods, improvement of agrophysical, agrochemical and microbiological, also, extensive scientific research is carried out to increase the yield of vegetable crops in various irrigation methods and reduce the phytosanitary status of the field (the density of weeds and pests, the degree of disease). Development, improvement and wide introduction into practice of optimal economical irrigation methods in the care of planting vegetable crops in spring and summer terms in conditions of water shortage is one of the pressing issues in agriculture
Keywords: Economical methods of irrigation; rut